RETRACTED: Modelling demand response in smart microgrid with techno and economic objective functions and improvement of network efficiency - Wang Xuan; Zhang Xiaofeng; Zhou Feng; Xu Xiang; Allathadka H.P. (Science and Technology for Energy Transition)
Following the publication of the Retraction Notice, the article was formally retracted on 29 January 2025. The Publisher and Editors in Chief received an allegation of plagiarism for this article published recently in STET. The investigation into this allegation has confirmed a very high rate of similarity with an article currently under peer review in the journal Electrical Engineering consistent with the alleged plagiarism, and the anteriority of the submission in Electrical Engineering. Every submitted manuscript to STET is compared to published papers in order to detect similarities. However, in the present case the paper in question was still under evaluation. The authors of the article published in STET have not provided convincing answers concerning their contribution to the work and have not provided an explanation for the excessive similarity. The Publisher and Editors have concluded to the truth of the allegation and have decided to retract this article.